(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
The article analyzes the factors that strengthen the civic position of young people within the framework of the concept “New Uzbekistan – a new legal consciousness”. Legal consciousness is explained as the unity of (i) awareness of one’s rights and freedoms, duties and responsibility, (ii) a value‑based attitude toward the law, and (iii) law‑abiding (legal) behavior. It is argued that legal education, moral upbringing based on national values, the institutions of the family and the mahalla, mass media, and civil‑society organizations—through their coordinated cooperation—play a decisive role in forming an active civic stance among youth.